The effects of land-use change and management on soil nitrous oxide emissions from Miscanthus x giganteus - Roth, Brendan (Trinity College (Dublin, Ireland). Department of Botany, 2011)
The use of bioenergy crops as fossil fuel replacements has expanded in the recent past and is likely to continue to grow in the near future as countries attempt to meet greenhouse gas reduction targets outlined in various policies. Miscanthus x giganteus is a tropical C4 grass which is being increasingly exploited as an energy crop due to its substantial yields in temperate climates and low nitrogen input requirements. While Miscanthus has been subject to much research little is known about its relationship with soil N2O emissions. Here the effects of land-use change from grassland to Miscanthus, as well as nitrogen fertiliser management, on soil N2O emissions have been investigated. Additionally the suitability of the process based model DNDC for simulating N2O emissions from Miscanthus was assessed. Two separate twelve-month field trials were carried out at the Teagasc Oak Park Research Centre, Co. Carlow. The effects of land-use change were examined by measuring N2O emissions, soil NO3 and NH4+ concentrations, and soil temperature and water filled pore space from a grassland, newly planted Miscanthus crop, and long established Miscanthus crop. Similarly the effects of fertiliser addition were examined by measuring the same parameters from a long established Miscanthus crop subject to nitrogen fertiliser application rates of 0, 63, and 125 kg-N ha-1. Data collected during these trials were used to parameterise, run, and validate the process-based model DNDC.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.